PERAN ORANG TUA DALAM MENINGKATKAN KEDISIPLINAN DAN TANGGUNG JAWAB SISWA SEKOLAH DASAR (SD) DI KORONG RIMBO KARAMBIA, KECAMATAN ULAKAN TAPAKIS, KABUPATEN PADANG PARIAMAN - Silvia Herlina (Ensiklopedia Education Review, 2020)
This study aims to describe the form of the role of parents in improving discipline and responsibility for children who are still in elementary school (SD) in Korong rimbo karambia, ulakan tapakis sub-district, padang pariaman district, as well as to find out the inhibiting factors for planting discipline and responsibility. answer to elementary school students in Korong rimbo karambia, ulakan tapakih sub-district, padang pariaman district. This study uses a qualitative approach with descriptive analysis research type. The research focus is a form of child discipline. The activity stage is the planning stage, the implementation stage, and the report result stage, the data sources used are primary and secondary data. The instrument used in this study was an interview guide sheet, data collection procedures, namely observation, interviews and documentation. Checking the validity of the data, namely the triangulation of techniques and triangulation of sources, while the data analysis used was to explain, describe, and describe according to the problem. The results showed that (1) parents still supervise their children both in terms of time and behavior, (2) the inhibiting factor in instilling discipline and responsibility for elementary school students, namely the lack of consistency of parents in providing examples due to the busyness of parents at work.